Dictyostelium discoideum: A Model System for Cell and Developmental Biology. Issue 15 (9th November 2017) - Mathavarajah, Sabateeshan; Flores, Ana; Huber, Robert J.
Abstract: The social amoeba Dictyostelium discoideum has long served as a model system for studying fundamental processes in cell and developmental biology. This eukaryotic microbe is also recognized as a model organism for biomedical and human disease research since the genome encodes homologs of genes linked to human disease, such as those linked to cancer and neurodegeneration. Dictyostelium has a unique life cycle composed of a unicellular growth phase and a multicellular developmental phase that is induced by starvation. During its life cycle, Dictyostelium undergoes conserved cellular processes including, but not limited to, cell proliferation, phagocytosis, intercellular signaling, cell adhesion and motility, chemotaxis, and cell differentiation. The history of the organism, the resources available to researchers in the community, and the diverse ways that Dictyostelium is used in the contemporary research lab are discussed. © 2017 by John Wiley & Sons, Inc.